Pengaruh Bimbingan Orangtua Terhadap Minat Belajar Anak Usia 5-6 Tahun di TK Cerdas Ceria Tapian Nauli Kecamatan Sipoholon Tahun Pembelajaran 2022/2023 - Raya Simamora; Uranus Zamili; Rotua Samosir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to determine the positive and significant influence of parental guidance on the interest in learning of children aged 5-6 years at the Smart Ceria Tapian Nauli Kindergarten, Sipoholon District, for the 2022/2023 Academic Year. The family here is the center for the development of all activities, both learning activities and other activities that can develop the child's interest in learning. The method used in this research is a descriptive quantitative research method. The population is all children aged 5-6 years at the Smart Ceria Tapian Nauli Kindergarten, Sipoholon District, 2022/2023 Academic Year, totaling 38 people and a sample of 20 people was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a positive closed questionnaire of 30 items. The results of the data analysis show that there is a positive and significant influence of parental guidance on the interest in learning of children aged 5-6 years at the Smart Ceria Tapian Nauli Kindergarten, Sipoholon District, 2022/2023 Academic Year: 1) Test the analysis requirements: a) test a positive relationship to obtain a value rxy = 0.673 > rtable(=0.05,n=20) = 0.444, thus it is known that there is a positive relationship between variable .05,dk=n-2=18)= 2.101, thus there is a significant relationship between variable The regression equation Y ̂=